Disjointing Technique for Reliability Evaluation of Computer-Communication Networks - Kaushik, Kriti; Pahuja, G.L. (Procedia computer science, 2015)
Source to all terminal reliability of a network is the ability of the network to transmit the commodity from source node to all other terminal nodes. The paper proposes an algorithm for source to all terminal reliability evaluation of directed networks. The algorithm starts with a spanning tree which is termed as first spanning tree (FST). All other disjoint spanning trees are generated from the knowledge of first spanning tree. Source to all terminal reliability is evaluated by taking probability of union of disjoint spanning trees. The method puts no constraint on FST selection. The proposed method is fast, efficient and no failed spanning tree is generated. The algorithm doesn’t generate duplicate spanning trees. The method is explained with the help of an example. The advantage in terms of computational complexity is also compared with the existing techniques.